Impact of Logging on non Timber Forest Products (ntfps) in the Rainforest of South Eastern Nigeria - Mfon, Philip; Bisong, Francis E. (Mediterranean Journal of Social Sciences, 2011)
This study examined the impact of logging intensity on forest diversity in Iwuru, Akamkpa Local Government Area ofCross River State, South Eastern Nigeria. Specifically, it considered the effects of logging intensity on availability of non-timber forestproducts (NTFPs), which include timber species and non-timber tree species as well as shrubs and climber species with NTFPs values.The study depended largely on the collection of primary data through direct field measurements carried out during forest inventory exercisesin sample plots with lightly logged, moderately logged, severely logged and unlogged tropical rainforest in the study area (Iwuru). Theunlogged sample plots were of various sizes depending on the type and quantity of samples to be considered. The collected data wereanalysed using two types of analytical statistical models, that is, statistical means and analysis of variance (ANOVA).From thestatistical mean analysis, the mean value for NTFPs ascribed as â€œgoodâ€ decreases from unlogged sample plots (31.40), through lightlylogged (13.68) to moderately logged (4.71) and intensively logged plots (0.79).However, more species recorded as â€œminimalâ€, â€œmoderateâ€and â€œsevereâ€ were in highly logged plots. The result from the analysis of variance indicates a relatively high f-value of 4.749 and very lowp-value of 0.003 indicating a significant relationship between logging and availability of NTFPs. It is established that logging intensitysignificantly affects the quality and quantity of NTFPs. The policy implications of findings are explored.